2022
DOI: 10.21037/gs-22-234
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune-related biomarkers for predicting neoadjuvant chemotherapy sensitivity in HER2 negative breast cancer via bioinformatics analysis

Abstract: Background: Neoadjuvant chemotherapy (NAC) is an important treatment for breast cancer (BC) patients.However, due to the lack of specific therapeutic targets, only 1/3 of human epidermal growth factor receptor 2 (HER2)-negative patients reach pathological complete response (pCR). Therefore, there is an urgent need to identify novel biomarkers to distinguish and predict NAC sensitive in BC patients.Methods: The GSE163882 dataset, containing 159 BC patients treated with NAC, was downloaded from the Gene Expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Several previous studies have also demonstrated the association of chemotherapy efficacy with immune system‐related expression profiles or immune cell infiltration in preNAC biopsy samples. Fang et al identified immune‐related biomarkers predictive of NAC efficacy by using gene expression profiles of breast cancer patients 26 . The genes identified in their report, such as CXCL9 , CXCL10 , CXCL11 , CXCL13 , GZMB , IDO1 , and LYZ , were very similar to those in our study, suggesting a shared biological mechanism for chemosensitivity between esophageal and breast cancers.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Several previous studies have also demonstrated the association of chemotherapy efficacy with immune system‐related expression profiles or immune cell infiltration in preNAC biopsy samples. Fang et al identified immune‐related biomarkers predictive of NAC efficacy by using gene expression profiles of breast cancer patients 26 . The genes identified in their report, such as CXCL9 , CXCL10 , CXCL11 , CXCL13 , GZMB , IDO1 , and LYZ , were very similar to those in our study, suggesting a shared biological mechanism for chemosensitivity between esophageal and breast cancers.…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, we also found that some CD68‐negative stromal cells (non‐macrophage stromal cells) also expressed CXCL9 (Figure 5D–F ). Considering that previous reports have suggested T cells as the source of CXCL9, 25 , 26 it is possible that T cells in the biopsy samples also expressed CXCL9. Further studies are required to address this possibility.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…CXCL10 and CXCL11 are proinflammatory cytokines that promote antitumour immunity 45 and were found to be associated with the prevention of M2 macrophage polarisation in PDAC 46 47 and glioblastoma. 48 In addition, elevated levels of these cytokines were associated with an improved (immunological) response to nCRT in rectal cancer 49 and breast cancer 50 and positively correlated to prolonged survival in PDAC patients treated with chemotherapy. 51 In contrast, elevated serum levels of the cytokine CCL2 were found to be associated with poor PDAC survival, 52 and both CCL2 and IL34 promote M2 macrophage polarisation.…”
Section: Discussionmentioning
confidence: 99%